Sistema fotovoltaico autônomo utilizando configuração multi-string e inversor multinível - Desconzi, Matheus Iensen (2011)
The continuous economic development of many countries and the emerging environmental issues (gas emissions and the greenhouse effect) observed in the last decades forced an intense research in renewable energy sources. Hydro, photovoltaic (PV) and wind energy conversion are the most explored technologies due to their considerable advantages, such as reliability, low environmental impact and capability to support microgrid systems or to connect to the electric grid. Among these energy sources the PV is pointed out as one of the most modular and environmentally friendly technologies. Furthermore, this technology enabled, by means of stand-alone or off-grid systems, the access of electricity in many communities distant form the grid, and even in difficult access remote applications. However, the PV panel still represents low efficiency and high cost, making imperative the use of efficient and reliable energy processing stages. Therefore, this work proposes a stand-alone photovoltaic system with decentralized configuration, aiming a high energy yield. For the output stage, a multilevel inverter was chosen, aggregating the intrinsic advantages that these converters present. The analysis of each energy processing stage is presented, as well as the modeling and control of the employed converters. Due to the requirement of a backup system (in stand-alone systems), a decentralized configuration of the battery bank is proposed. Moreover, aiming to optimize the backup system lifetime and reduce the maintenance costs, a controlled charge/discharge process on the batteries is implemented. Simulation and experimental results are presented, verifying the functionality of the proposed structure.